Injury patterns and associated demographics of intimate partner violence in men presenting to U.S. emergency departments. Issue 3 (16th December 2021) - Khurana, Bharti; Hines, Denise A.; Johnson, Benjamin A.; Bates, Elizabeth A.; Graham‐Kevan, Nicola; Loder, Randall T.
Abstract: Research suggests that there are differences between sexes in physical intimate partner violence (IPV) victimization that could lead to different injury patterns. In addition, research shows that men under‐report their injuries yet may suffer grave consequences. It is, thus, vital to establish physical injury patterns in male IPV victims. A retrospective review of prospectively collected data was performed using the National Electronic Injury Surveillance System‐All Injury Program data from 2005 to 2015 for all IPV‐related injuries in both male and female patients. Sex differences by demographics, mechanism, anatomic location, and diagnoses of IPV injuries were analyzed using statistical methods accounting for the weighted stratified nature of the data. IPV accounted for 0.61% of all emergency department visits; 17.2% were in males and 82.8% in females. Male patients were older (36.1% vs. 16.8% over 60 years), more likely to be Black (40.5% vs. 28.8%), sustained more injuries due to cutting (28.1% vs. 3.5%), more lacerations (46.9% vs. 13.0%), more injuries to the upper extremity (25.8% vs. 14.1%), and fewer contusions/abrasions (30.1% vs. 49.0%), compared to female IPV patients ( p  < .0001). There were also more hospitalizations in men (7.9% vs. 3.7% p  = .0002). Knowledge of specific IPV‐related injury characteristics in men will enable healthcare providers to counteract underreporting of IPV.